2020
DOI: 10.12659/msm.923195
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Metabolite 3-Iodothyronamine (T1AM) Alleviates Hypoxia/Reoxygenation-Induced Cardiac Myocyte Apoptosis via Akt/FoxO1 Pathway

Abstract: Background: The thyroid hormone metabolite 3-iodothyronamine (T1AM) is rapidly emerging as promising compound of decreasing heart rate and lowering cardiac output. The aim of our study was to fully understand the molecular mechanism of T1AM on cardiomyocytes and its potential targets in cardiovascular diseases. Material/Methods: We developed an in vitro myocardial ischemia-reperfusion injury model of AC-16 cells by hypoxia-reoxygenation injury. Cell viability of AC-16 cells was detected using CCK-8 assay and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Our previous study examined the effects of T1AM on H/ R-induced AC-16 cells. Based on both RNA-seq and cellbased assays, T1AM was shown to mediate hypometabolism and exert protective effects on cardiomyocytes via regulation of the FoxO signaling pathway (12,15). However, limited studies have reported the protective role of T1AM in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study examined the effects of T1AM on H/ R-induced AC-16 cells. Based on both RNA-seq and cellbased assays, T1AM was shown to mediate hypometabolism and exert protective effects on cardiomyocytes via regulation of the FoxO signaling pathway (12,15). However, limited studies have reported the protective role of T1AM in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has therapeutic potential for the treatment of metabolic (10), cardiovascular (11,12), and neurological diseases (13,14). Our previous RNA-sequencing data and in vitro myocardiocytes model demonstrated that T1AM protects cardiomyocytes against hypoxia/reoxygenation (H/R) induced cell injury in AC-16 cells via regulation of the FoxO signaling pathway (15). Other studies have shown that administration of T1AM in the isolated heart limited MIRI (16).…”
Section: Introductionmentioning
confidence: 93%
“…However, T1AM produced a cardioprotective effect in isolated rat hearts in an experimental acute model of ischaemia-reperfusion injury, mediated by protein kinase C and the mitochondrial pathway (Frascarelli et al, 2011). Recently, it was shown that T1AM protected AC-16 cells against cell injury induced by hypoxia-reoxygenation via regulation of the FoxO signalling pathway (Zhou et al, 2020). Both metabolites are generated from decarboxylation and deiodination reactions and, therefore, the regulation of the local synthesis of these metabolites might also be important for their physiological effects (Louzada & Carvalho, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia is involved in the progression of multiple cardiovascular diseases including coronary artery disease, myocardial fibrosis, and heart failure [ 22 , 23 ]. Recently, METRNL, which is a newly discovered adipokine, was proven to be significantly associated with the pathogenesis of coronary artery disease [ 16 ].…”
Section: Discussionmentioning
confidence: 99%